Investigation of alpha-wave frequency characteristics in the patients with chronic tension headache and its modification during electromyographic-temperature training - O. S. Shubina; M. Ye. Melnikov; I. A. Veretelnikov (Бюллетень сибирской медицины, 2010)
Chronic tension headache is the most commonly experienced headache. Low effectiveness of its treatment is connected with lack of understanding of this disorder pathogenensis. It was shown that electromyographic-temperature training provoked modification of alpha-wave power and frequency: power of alpha increased, frequency of maximal increased as well.